Broadband microwave absorber constructed by reduced graphene oxide/La0.7Sr0.3MnO3 composites. Issue 71 (17th December 2019) - Yan, Kelan; Yin, Feng; Pang, Chao; Zuo, Xiuhui; Zhang, Qitu; Shen, Liming; Fan, Runhua; Bao, Ningzhong
Abstract : High-performance microwave absorbing materials require optimized impedance matching and high attenuation ability. To meet these requirements, rGO/ LSMO composites were prepared thereby incorporating electric loss with magnetic loss materials. Abstract : High-performance microwave absorbing materials require optimized impedance matching and high attenuation ability. Here we meet the challenge by incorporating electric loss with magnetic loss materials to prepare carbon-based/magnetic hybrids. The reduced graphene oxide (rGO)/La0.7 Sr0.3 MnO3 (LSMO) composites were prepared by dispersing the LSMO powders into 4.25, 6.25, 8.16, and 10 wt% of the graphene oxide aqueous solution, then the rGO/LSMO composites were formed by hydrothermal method. The pure rGO, LSMO, and rGO/LSMO composites were studied using X-ray diffraction and SEM. Microwave absorption properties were investigated by using coin method. Simulation studies show that 6.25 wt% of rGO/LSMO in a wax matrix exhibits the strongest reflection loss of −47.9 dB @ 10.7 GHz at a thickness of 2.5 mm. Moreover, the effective absorption bandwidth with the reflection loss below −10 dB is up to 14.5 GHz, ranged from 3.5 to 18 GHz for the composites with a thickness of 1.5–5.5 mm, due to a synergism between dielectric loss of rGO and magnetic loss of magnetic LSMO, which is an interesting exploration in the applications of rGO and LSMO. This method can be extended to design and fabricate hybrid absorbers with effective microwave absorption.